Nuevos datos sobre el Ramillete de flores divinas (México, 1605) de Bernardo de la Vega. Estudio del único ejemplar conocido de la obra - Stein, Tadeo Pablo; Cacho Casal, Rodrigo (El Colegio de México, 2024)
This article brings to light the only Known copy of Bernardo de la Vega’s Ramillete de flores divinas. Published in Mexico City in 1605,and written by a man who was born in Spain but who settled in the New World, this collection of religious poems was up until now thought to be lost. An examination of this volume allows us to reassess significant issues with regards to the authorship of the work as well as of others attributed to Bernardo de la Vega (some of them printed in Spain, others in New Spain). At the same time we are also able to make an important contribution to current knowledge of the development of poetry in the capital city of New Spain in the early seventeenth century.